Atomic processes modeling of X-ray free electron laser produced plasmas using SCFLY code - Chung, H; Cho, B; Ciricosta, O; Vinko, S; Wark, J; Lee, R (AIP Publishing, 2017)
With the development of X-ray free electron lasers (XFEL), a novel state of matter of highly transient and non-equilibrium plasma has been created in laboratories. As high intensity X-ray laser beams interact with a solid density target, electrons are ionized from inner-shell orbitals and these electrons and XFEL photons create dense and finite temperature plasmas. In order to study atomic processes in XFEL driven plasmas, the atomic kinetics model SCFLY containing an extensive set of configurations needed for solid density plasmas was applied to study atomic processes of XFEL driven systems. The code accepts the time-dependent conditions of the XFEL as input parameters, and computes time-dependent population distributions and ionization distributions self-consistently with electron temperatures and densities assuming an instantaneous equilibration of electron energies. The methods and assumptions in the atomic kinetics model and unique aspects of atomic processes in XFEL driven plasmas are described.